Monetary policy, fiscal policies, and labour markets : macroeconomic policymaking in the EMU - Beetsma, Roel M. W. J. (Cambridge, UK ; New York, NY, USA : Cambridge University Press, 2004)
The book offers one of the most comprehensive surveys of research in macroeconomic policymaking within the EMU today.
Includes bibliographical references and index.
rua 13/02/15; oif 07/04/15
Loans
Keywords: Monetary policy; Fiscal policy; Monetary unions; European union countries